Design and Development of a Web-Based Employee Attendance and Payroll Information System at CV Expressa - Wanda Fadillah; Hanifah Permatasari; Moh. Muhtarom (Universitas PGRI Adi Buana Surabaya, 2025)
This study aims to design and build a web-based employee attendance and payroll information system at CV Expressa to overcome problems arising from manual processes, such as late salaries, data recapitulation errors, and lack of transparency. The method used is the System Development Life Cycle (SDLC) waterfall model approach, which includes needs analysis, system design, implementation using the Laravel framework and MySQL database, testing with the blackbox method, and maintenance. The results of the study show that the system built is able to automate GPS-based attendance recording and salary calculations, accelerate data recapitulation, and provide independent payslip access for employees. This system also succeeded in increasing operational efficiency and data accuracy, as well as reducing administrative workload. However, this study has limitations in the scope of implementation which is still limited to one company and does not include advanced security features such as biometric authentication and mobile applications. Further development is recommended to improve the scalability and flexibility of the system.